Preparation method and application of bismuth nanocarbon sphere modified electrode for liquid flow battery
By using bismuth nanocarbon ball modification technology on the flow battery electrode, the problem of insufficient electrochemical performance of existing electrode materials is solved, higher power density and longer cycle life are achieved, and the overall performance of flow battery is improved .
Patent Information
- Application Number
- CN202410332105.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-22
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-03-22
AI Technical Summary
The electrochemical performance and redox kinetics of existing flow battery electrode materials are insufficient, resulting in low power density, high investment cost and side reactions, limiting the commercial development of flow battery.
The preparation method of bismuth nanocarbon spheres is adopted to modify the electrode, and the bismuth nanocarbon spheres are anchored on the electrode surface through two steps of hydrothermal reaction and high-temperature carbonization, which increases the active site and specific surface area, and improves the electrochemical performance of the electrode.
It significantly improves the power density, charge and discharge performance and cycle life of the flow battery, reduces the polarization of the electrode, uniforms the local current density, and improves the energy efficiency.
Smart Images

Figure CN118213542B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of liquid flow batteries, and in particular to a preparation method and application of a bismuth nano-carbon ball modified electrode for a liquid flow battery. Background Art
[0002] In recent years, the proportion of renewable energy-based power generation devices in the number of newly added power generation installations has gradually increased. This trend shows that renewable energy is gradually replacing traditional thermal power generation. At present, although common renewable energy sources such as wind energy, solar energy, and tidal energy are gradually being developed on a large scale, their intermittent and volatile problems have become challenges and obstacles to their further rapid development. Direct grid connection will not only cause an impact on the power grid system, but also endanger the normal power supply output to the user side, thereby creating safety hazards and affecting the normal work and life of users. Therefore, there is an urgent need for a suitable and safe energy storage system to regulate and stabilize the power output of renewable energy generation. Among the many energy storage systems, redox flow batteries have attracted much attention from researchers because of their high safety, good scalability, long cycle life, flexible design, and power and energy decoupling. Among the many flow battery systems developed by researchers, iron-chromium flow batteries and all-vanadium flow batteries, as common types of flow battery systems, are being widely developed, but the problems of hydrogen and oxygen evolution side reactions and investment costs currently faced have seriously restricted their further commercial development.
[0003] As an important component of the flow battery system, the electrode is the place where the electrochemical reaction occurs. The richness of its active sites and the size of its specific surface area can not only restrict the redox reaction of the active substance, but also determine the electrochemical performance of the electrode. Graphite felt, carbon felt, carbon paper and carbon cloth are widely used as flow battery electrode materials due to their good mechanical stability, high conductivity, corrosion resistance and low cost. However, their poor electrochemical performance and redox kinetics restrict the power density of the flow battery, increase the investment cost of the system, and lead to a series of problems such as side reactions. Therefore, in order to solve the above problems, the porous electrodes in the flow battery need to be further designed and optimized. The modification methods of porous electrodes can be roughly divided into three categories, namely functional group modification, surface etching and catalyst modification. Functional group modification such as oxygen functional group and nitrogen functional group can increase the hydrophilicity of the electrode to a certain extent, but the degree of improvement of active sites and specific surface area is limited. Surface etching can increase the specific surface area of the electrode to a certain extent, but the elements used for etching often remain on the electrode surface and bring side reactions during battery operation. Catalyst modification is an effective electrode modification method. It can not only increase the number of active sites on the electrode surface, improve the specific surface area, and increase the hydrophilicity of the electrode, but also can catalyze the redox reaction of active substances in a targeted and directional manner. Therefore, it has been widely developed by researchers. However, the development of catalysts currently faces many problems, such as the stability of catalysts during long-term operation of batteries, the corrosion resistance of catalysts under acidic electrolyte conditions, the development and maintenance costs of catalysts, the deactivation of catalysts during battery operation, and the further optimization of the overall performance of catalysts on electrodes. To this end, it is necessary to further develop, design and optimize the types and forms of catalysts to improve the electrochemical properties of electrodes, the overall charge and discharge performance of batteries, and the power density.
[0004] In order to solve the above problems, the present invention proposes a preparation method and application of a bismuth nano-carbon ball modified electrode for a liquid flow battery. Summary of the invention
[0005] 1. Technical Problems to be Solved by the Present Invention
[0006] The purpose of the present invention is to propose a preparation method and application of a bismuth nano-carbon ball modified electrode for a liquid flow battery to solve the problems raised in the background technology, by greatly increasing the number of active sites of the electrode, improving the specific surface area, and promoting the redox reaction of the catalytic active substance on the electrode surface, thereby improving the overall charge and discharge performance, power density and cycle life of the battery.
[0007] 2. Technical solution
[0008] To achieve the above object, the present invention provides the following technical solutions:
[0009] The method for preparing a bismuth nanocarbon ball modified electrode for a liquid flow battery comprises the following steps:
[0010] S1. Select appropriate amounts of bismuth nitrate pentahydrate and trimesic acid as solutes, select appropriate amounts of N,N-dimethylformamide and methanol as solvents, mix and stir the solute and the solvent to obtain a precursor hydrothermal reaction solution;
[0011] S2, transferring the precursor hydrothermal reaction solution prepared in S1 to a hydrothermal reactor, placing an electrode, setting a reaction temperature for a hydrothermal reaction, and generating a precursor modified electrode;
[0012] S3. Transfer the precursor modified electrode prepared in S2 to a tubular furnace for high-temperature carbonization to obtain a bismuth nanocarbon sphere modified electrode.
[0013] Preferably, the amount of the solute in S1 is: bismuth nitrate pentahydrate is 0.95-1.00 mmol, and trimesic acid is 1.18-2.94 mmol; the total volume of the solvent is fixed at 20 mL, wherein the ratio of N,N-dimethylformamide to methanol is 1:0 or 4:1 or 1:3.
[0014] Preferably, the electrode placed in S2 is graphite felt or carbon felt, and its thickness is 2.0-4.6 mm.
[0015] Preferably, the hydrothermal reaction temperature in S2 is 120° C., and the reaction time is 12 to 24 hours.
[0016] Preferably, the electrode generated after the hydrothermal reaction in S2 is a precursor-modified graphite felt or carbon felt electrode.
[0017] Preferably, the atmosphere of the tube furnace in S3 is N2 atmosphere, the carbonization temperature is 800-1000°C, the heating rate is 4-6°C / min, and the high temperature duration is 1.5-2.5h.
[0018] The bismuth nano-carbon ball modified electrode prepared by the above method is used in the preparation of all-vanadium liquid flow battery and iron-chromium liquid flow battery negative electrode.
[0019] 3. Beneficial effects
[0020] (1) The present invention combines hydrothermal synthesis and high-temperature carbonization. The prepared bismuth nanocarbon spheres are anchored on the electrode surface and have the characteristics of large specific surface area, rich active sites, stable structure and excellent performance. The liquid flow battery can operate at a higher current density, greatly improving its power density.
[0021] (2) The present invention can reduce the polarization of the electrode and make its local current density uniform, so that the all-vanadium liquid flow battery and the iron-chromium liquid flow battery can achieve the same current density at 300 mA cm -2 The energy efficiencies at different current densities reached 80.4 and 80.2%, respectively.
[0022] (3) The present invention does not change the macroscopic electrode structure, does not affect the original assembly of the electrode, and does not affect the original battery structure.
[0023] (4) The present invention is simple to operate and the cost of raw materials is economical. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 (a) Scanning electron microscope image of a conventional untreated electrode; (b) Scanning electron microscope image of a conventional heat-treated electrode; (c) Scanning electron microscope image of a bismuth nanocarbon ball modified electrode for a liquid flow battery proposed in the present invention;
[0025] Figure 2 The bismuth nanocarbon ball modified electrode and the heat-treated electrode of the present invention are used in the examples at 300 mA cm -2 Comparison of charge and discharge curves under current density;
[0026] Figure 3 The bismuth nanocarbon ball modified electrode and the untreated and heat-treated electrodes of the present invention are shown in the examples at 100-600 mA cm -2 Performance comparison under different current densities. DETAILED DESCRIPTION
[0027] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the accompanying drawings.
[0028] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0029] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0030] Principle description: In the modification design of porous electrodes of liquid flow batteries, the effect of catalyst modification on its performance improvement is more obvious. By increasing the number of active sites, specific surface area and hydrophilicity on the electrode surface, the catalyst can enable the porous electrodes of liquid flow batteries to achieve better electrochemical reaction activity and directionally catalyze the redox reaction occurring on the electrode surface, thereby improving the charge and discharge performance and power density of the battery. In the present invention, a bismuth-based catalyst is selected to structurally modify the electrode, which has the characteristics of good electrocatalytic activity, conductivity, stability and flexible adjustability. The present invention anchors bismuth nanocarbon balls on the electrode surface through a two-step operation of hydrothermal reaction and high-temperature carbonization, which not only enriches the number of active sites and increases the reaction specific surface area, but also has a stable structure and excellent performance, greatly reduces the polarization degree of the electrode surface, and evens out the local current density on the electrode surface, so that the liquid flow battery can operate stably at a higher current density and improve its energy efficiency and power density.
[0031] Based on the above content, the preparation method and application of a bismuth nano-carbon ball modified electrode for a liquid flow battery proposed by the present invention are described in combination with specific embodiments. The specific content is as follows.
[0032] Embodiment 1:
[0033] This embodiment discloses a preparation method and application of a bismuth nanocarbon ball modified electrode for a flow battery, wherein the preparation method of the bismuth nanocarbon ball modified electrode includes two parts, namely, hydrothermal reaction synthesis of a precursor and high-temperature carbonization of the precursor modified electrode. The solute in the solution of the precursor hydrothermal reaction is bismuth nitrate pentahydrate and trimesic acid, and the solvent is N, N-dimethylformamide and methanol. The solute bismuth nitrate pentahydrate in the solution is 0.98mmol, and the trimesic acid is 1.18mmol; the total volume of the solvent is fixed to 20mL, and the ratio of N, N-dimethylformamide to methanol is 4:1. The prepared solution is transferred to a hydrothermal reactor and an electrode is placed in it. The type of electrode placed in the hydrothermal reaction is graphite felt or carbon felt, and its thickness is 3mm. The hydrothermal reaction temperature is 120℃, and the time is 24h. After the hydrothermal reaction, a graphite felt or carbon felt electrode modified by the precursor is obtained. The high-temperature carbonization of the precursor modified electrode is carried out in a tubular furnace. The atmosphere of the tube furnace is N2 atmosphere, the carbonization temperature is 800℃, the heating rate is 5℃ / min, and the high temperature duration is 2h. After high temperature carbonization, a bismuth nanocarbon ball modified electrode is obtained, which is used as a negative electrode in all-vanadium liquid flow batteries.
[0034] The bismuth nanocarbon ball modified electrode prepared by the above preparation method is used as the negative electrode in the all-vanadium redox flow battery, and the charge and discharge performance test is carried out. The negative electrode adopts the bismuth nanocarbon ball modified electrode prepared by the present invention, the positive electrode adopts the heat-treated graphite felt, the heat treatment condition is 400℃ for 10h, the diaphragm adopts Nafion 212, and the negative electrode electrolyte is 1M V3+ +3M H2SO4, the positive electrolyte is 1M VO 2+ +3M H2SO4. At 300mA cm -2 Under the current density, the energy efficiency of the all-vanadium redox flow battery composed of the self-supporting bismuth nanosheet modified electrode of the present invention is 79.2%, and the electrolyte utilization rate is 75.2%.
[0035] Embodiment 2:
[0036] This embodiment discloses a preparation method and application of a bismuth nanocarbon ball modified electrode for a flow battery, wherein the preparation method of the bismuth nanocarbon ball modified electrode includes two parts, namely, hydrothermal reaction synthesis of a precursor and high-temperature carbonization of the precursor modified electrode. The solute in the solution of the precursor hydrothermal reaction is bismuth nitrate pentahydrate and trimesic acid, and the solvent is N, N-dimethylformamide and methanol. The solute bismuth nitrate pentahydrate in the solution is 0.98mmol, and the trimesic acid is 1.84mmol; the total volume of the solvent is fixed to 20mL, and the ratio of N, N-dimethylformamide to methanol is 4:1. The prepared solution is transferred to a hydrothermal reactor and an electrode is placed in it. The type of electrode placed in the hydrothermal reaction is graphite felt or carbon felt, and its thickness is 3mm. The hydrothermal reaction temperature is 120℃, and the time is 24h. After the hydrothermal reaction, a graphite felt or carbon felt electrode modified by the precursor is obtained. The high-temperature carbonization of the precursor modified electrode is carried out in a tubular furnace. The atmosphere of the tube furnace is N2 atmosphere, the carbonization temperature is 800℃, the heating rate is 5℃ / min, and the high temperature duration is 2h. After high temperature carbonization, a bismuth nanocarbon ball modified electrode is obtained, which is used as a negative electrode in all-vanadium liquid flow batteries.
[0037] The bismuth nanocarbon ball modified electrode prepared by the above preparation method is used as the negative electrode in the all-vanadium redox flow battery, and the charge and discharge performance test is carried out. The negative electrode adopts the present invention, the positive electrode adopts heat-treated graphite felt, the heat treatment condition is 400℃ for 10h, the diaphragm adopts Nafion 212, and the negative electrode electrolyte is 1M V 3+ +3M H2SO4, the positive electrolyte is 1M VO 2+ +3MH2SO4. At 300mA cm -2 Under the current density, the energy efficiency of the all-vanadium liquid flow battery composed of the self-supporting bismuth nanosheet modified electrode of the present invention is 80.4%, and the electrolyte utilization rate is 73.8%.
[0038] Embodiment 3:
[0039] This embodiment discloses a preparation method and application of a bismuth nanocarbon ball modified electrode for a flow battery, wherein the preparation method of the bismuth nanocarbon ball modified electrode includes two parts, namely, hydrothermal reaction synthesis of a precursor and high-temperature carbonization of the precursor modified electrode. The solute in the solution of the precursor hydrothermal reaction is bismuth nitrate pentahydrate and trimesic acid, and the solvent is N, N-dimethylformamide and methanol. The solute bismuth nitrate pentahydrate in the solution is 0.98mmol, and the trimesic acid is 2.94mmol; the total volume of the solvent is fixed to 20mL, and the ratio of N, N-dimethylformamide to methanol is 4:1. The prepared solution is transferred to a hydrothermal reactor and an electrode is placed. The type of electrode placed in the hydrothermal reaction is graphite felt or carbon felt, and its thickness is 3mm. The hydrothermal reaction temperature is 120°C and the time is 24h. After the hydrothermal reaction, a graphite felt or carbon felt electrode modified by the precursor is obtained. The high-temperature carbonization of the precursor modified electrode is carried out in a tubular furnace. The atmosphere of the tube furnace is N2 atmosphere, the carbonization temperature is 800℃, the heating rate is 5℃ / min, and the high temperature duration is 2h. After high temperature carbonization, a bismuth nanocarbon ball modified electrode is obtained, which is used as a negative electrode in all-vanadium liquid flow batteries.
[0040] The bismuth nanocarbon ball modified electrode prepared by the above method is used as the negative electrode in the all-vanadium redox flow battery, and the charge and discharge performance test is carried out. The negative electrode adopts the present invention, the positive electrode adopts heat-treated graphite felt, the heat treatment condition is 400℃ for 10h, the diaphragm adopts Nafion 212, and the negative electrode electrolyte is 1M V 3+ +3M H2SO4, the positive electrolyte is 1M VO 2+ +3M H2SO4. At 300mAcm -2 Under the current density, the energy efficiency of the all-vanadium redox flow battery composed of the self-supporting bismuth nanosheet modified electrode of the present invention is 79.7%, and the electrolyte utilization rate is 68.6%.
[0041] Comparative Example 1:
[0042] This comparative example provides an all-vanadium liquid flow battery assembled by conventional heat-treated electrodes, wherein both the negative electrode and the positive electrode are made of conventional heat-treated graphite felt, the heat treatment condition is 400°C for 10h, the diaphragm is Nafion 212, and the negative electrode electrolyte is 20mL 1M V 3+ +3M H2SO4, the positive electrolyte is 20mL 1M VO 2+ +3M H2SO4. At 300mA cm -2 Under the current density, the energy efficiency of the all-vanadium liquid flow battery composed of the conventional heat-treated electrodes of this comparative example is 66.3%, and the electrolyte utilization rate is 42.3%.
[0043] Comparative Example 2:
[0044] This comparative example provides an all-vanadium redox flow battery assembled from conventional untreated electrodes. Both the negative and positive electrodes are made of conventional untreated graphite felt, the separator is Nafion 212, and the negative electrode electrolyte is 20 mL 1M V 3+ +3M H2SO4, the positive electrolyte is 20mL 1M VO 2+ +3MH2SO4. At 100mA cm -2 At the current density of 300mAcm, the energy efficiency of the all-vanadium redox flow battery using the conventional untreated electrode composition of this comparative example is 61.5%, and the electrolyte utilization rate is 19.3%. -2 It cannot operate at current densities above 2000A.
[0045] Embodiment 4:
[0046] This embodiment discloses a preparation method and application of a bismuth nanocarbon ball modified electrode for a flow battery, wherein the preparation method of the bismuth nanocarbon ball modified electrode includes two parts, namely, hydrothermal reaction synthesis of a precursor and high-temperature carbonization of a precursor modified electrode. The solutes in the solution of the hydrothermal reaction of the precursor are bismuth nitrate pentahydrate and trimesic acid, and the solvents are N, N-dimethylformamide and methanol. The solute bismuth nitrate pentahydrate in the solution is 0.98mmol, and the trimesic acid is 1.18mmol; the total volume of the solvent is fixed to 20mL, and the ratio of N, N-dimethylformamide to methanol is 1:3. The prepared solution is transferred to a hydrothermal reactor and an electrode is placed in it. The type of electrode placed in the hydrothermal reaction is graphite felt or carbon felt, and its thickness is 3mm. The hydrothermal reaction temperature is 120°C and the time is 24h. After the hydrothermal reaction, a graphite felt or carbon felt electrode modified by the precursor is obtained. The high-temperature carbonization of the precursor modified electrode is carried out in a tubular furnace. The atmosphere of the tube furnace is N2 atmosphere, the carbonization temperature is 800℃, the heating rate is 5℃ / min, and the high temperature duration is 2h. After high temperature carbonization, a bismuth nanocarbon ball modified electrode is obtained, which is used as a negative electrode in all-vanadium liquid flow batteries.
[0047] The bismuth nanocarbon ball modified electrode prepared in this example was used as the negative electrode in an all-vanadium redox flow battery, and the charge and discharge performance test was performed. The negative electrode was the bismuth nanocarbon ball modified electrode prepared in this example, the positive electrode was the heat-treated graphite felt, the heat treatment condition was 400°C for 10h, the diaphragm was Nafion 212, and the negative electrode electrolyte was 1M V 3+ +3M H2SO4, the positive electrolyte is 1M VO 2+ +3M H2SO4. At 300mA cm -2 Under the current density, the energy efficiency of the all-vanadium redox flow battery composed of the self-supporting bismuth nanosheet modified electrode of the present invention is 78.2%, and the electrolyte utilization rate is 72.8%.
[0048] Comparative Example 3:
[0049] This comparative example provides an all-vanadium redox flow battery assembled with traditional heat-treated electrodes. Both the negative and positive electrodes are made of traditional heat-treated graphite felt, the heat treatment condition is 400℃ for 10h, the diaphragm is Nafion 212, and the negative electrode electrolyte is 20mL1M V 3+ +3M H2SO4, the positive electrolyte is 20mL 1M VO 2+ +3M H2SO4. At 300mA cm -2 Under the current density, the energy efficiency of the all-vanadium liquid flow battery composed of the conventional heat-treated electrodes of this comparative example is 66.3%, and the electrolyte utilization rate is 42.3%.
[0050] Embodiment 5:
[0051] This embodiment discloses a preparation method and application of a bismuth nanocarbon ball modified electrode for a flow battery, wherein the preparation method of the bismuth nanocarbon ball modified electrode includes two parts, namely, hydrothermal reaction synthesis of a precursor and high-temperature carbonization of the precursor modified electrode. The solute in the solution of the precursor hydrothermal reaction is bismuth nitrate pentahydrate and trimesic acid, and the solvent is N, N-dimethylformamide and methanol. The solute bismuth nitrate pentahydrate in the solution is 0.98mmol, and the trimesic acid is 1.84mmol; the total volume of the solvent is fixed to 20mL, and the ratio of N, N-dimethylformamide to methanol is 4:1. The prepared solution is transferred to a hydrothermal reactor and an electrode is placed in it. The type of electrode placed in the hydrothermal reaction is graphite felt or carbon felt, and its thickness is 3mm. The hydrothermal reaction temperature is 120℃, and the time is 24h. After the hydrothermal reaction, a graphite felt or carbon felt electrode modified by the precursor is obtained. The high-temperature carbonization of the precursor modified electrode is carried out in a tubular furnace. The atmosphere of the tube furnace is N2 atmosphere, the carbonization temperature is 800℃, the heating rate is 5℃ / min, and the high temperature duration is 2h. After high temperature carbonization, a bismuth nanocarbon ball modified electrode is obtained, which is used as a negative electrode in an iron-chromium liquid flow battery.
[0052] The bismuth nanocarbon modified electrode prepared in this example was used as the negative electrode in an iron-chromium flow battery, and the charge and discharge performance was tested. The negative electrode was the bismuth nanocarbon modified electrode prepared in this example, the positive electrode was the heat-treated graphite felt, the heat treatment condition was 400℃ for 10h, the diaphragm was Nafion 212, and the positive and negative electrolytes were 40mL 1M FeCl2+1MCrCl3+3M HCl. At 300mA cm -2 Under the current density, the energy efficiency of the all-vanadium redox flow battery composed of the self-supporting bismuth nanosheet modified electrode of the present invention is 80.2%, and the electrolyte utilization rate is 71.9%.
[0053] Comparative Example 4:
[0054] This comparative example provides an iron-chromium flow battery assembled with traditional heat-treated electrodes. Both the negative and positive electrodes use traditional heat-treated graphite felt, the heat treatment condition is 400℃ for 10h, the diaphragm uses Nafion 212, and the positive and negative electrolytes are 40mL 1M FeCl2+1MCrCl3+3M HCl. At 300mA cm -2 Under the current density, the energy efficiency of the iron-chromium flow battery composed of the conventional heat-treated electrodes of this comparative example is 69.7%, and the electrolyte utilization rate is 50.2%.
[0055] Based on the above embodiments and comparative examples, the bismuth nanocarbon ball modified electrode prepared by the present invention and its improvement on the performance of the flow battery are analyzed in conjunction with the accompanying drawings. The specific contents are as follows:
[0056] like Figure 1 As shown in the figure, (a) and (b) are graphite felt electrodes that have not been treated and have been treated using traditional heat treatment methods. Their surfaces are smooth and without any loaded substances. In contrast, (c) shows that there are obvious granular substances on the electrode surface, which are essentially bismuth nanocarbon balls prepared by the method disclosed in the patent. The bismuth nanocarbon balls are evenly attached to the electrode surface, providing the electrode with abundant active sites and increasing the specific surface area. At the same time, they can directional catalyze the redox reactions occurring in the battery, greatly improving the performance of the battery.
[0057] like Figure 2 As shown in the figure, the conventional heat-treated electrode and the bismuth nanocarbon ball modified electrode disclosed in the present invention are compared at 300 mA cm -2 The charge and discharge curve under current density. Compared with the traditional heat-treated electrode, the all-vanadium liquid flow battery assembled with bismuth nanocarbon ball modified electrode has a lower charging voltage and a higher discharge voltage, and has a larger specific capacity and makes more full use of the electrolyte. Compared with the traditional heat-treated electrode, its electrolyte utilization rate is 73.8%, which is 31.5% higher than the traditional heat-treated electrode.
[0058] like Figure 3 As shown in the figure, the coulombic efficiency, voltage efficiency and energy efficiency of the all-vanadium redox flow battery assembled with the untreated electrode, the conventional heat-treated electrode and the bismuth nano-carbon sphere modified electrode disclosed in the present invention are compared. Compared with the untreated electrode and the conventional heat-treated electrode, the battery assembled with the bismuth nano-carbon sphere modified electrode disclosed in the present invention can operate at a higher current density and has a higher efficiency. At 300mA cm -2 Under current density, the battery assembled with the bismuth nanocarbon ball modified electrode disclosed in the present invention has an energy efficiency of 80.4%, which is 14.1% higher than the efficiency of 66.3% of the heat-treated electrode. -2At the current density, its efficiency reached 75.6%, which was 18.1% higher than that of the heat-treated electrode.
[0059] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and improved concepts of the present invention within the technical scope disclosed by the present invention, and they should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a bismuth nanocarbon ball modified electrode for a flow battery, characterized in that: The following steps are involved: S1. Select appropriate amounts of bismuth nitrate pentahydrate and trimesic acid as solutes, select appropriate amounts of N,N-dimethylformamide and methanol as solvents, mix and stir the solute and the solvent to obtain a precursor hydrothermal reaction solution; S2, transferring the precursor hydrothermal reaction solution prepared in S1 to a hydrothermal reactor, placing an electrode, setting a reaction temperature for a hydrothermal reaction, and generating a precursor modified electrode; S3, transferring the precursor modified electrode prepared in S2 to a tube furnace for high-temperature carbonization to obtain a bismuth nanocarbon sphere modified electrode; In S1, the amount of bismuth nitrate pentahydrate is 0.95-1.00 mmol, and the amount of trimesic acid is 1.18-2.94 mmol; the total volume of the solvent is fixed at 20 mL, wherein the ratio of N,N-dimethylformamide to methanol is 1:0 or 4:1 or 1:3; In S2, the temperature of the hydrothermal reaction is 120°C and the reaction time is 12 to 24 h; In S3, the atmosphere of the tubular furnace is N2 atmosphere, the carbonization temperature is 800-1000°C, the heating rate is 4-6°C / min, and the carbonization time is 1.5-2.5 h.
2. The method for preparing a bismuth nanocarbon ball modified electrode for a flow battery according to claim 1, characterized in that: The type of electrode placed in S2 is graphite felt or carbon felt, and its thickness is 2.0 to 4.6 mm.
3. The method for preparing a bismuth nanocarbon ball modified electrode for a liquid flow battery according to claim 1, characterized in that: The electrode generated after the hydrothermal reaction in S2 is a graphite felt or carbon felt electrode modified by a precursor.
4. A bismuth nanocarbon sphere modified electrode prepared by the preparation method according to any one of claims 1 to 3.
5. Application of the bismuth nanocarbon ball modified electrode as claimed in claim 4 in the negative electrode of all-vanadium liquid flow battery and iron-chromium liquid flow battery.
Citation Information
Cited By
Multi-stage pore graphite felt for flow battery and preparation method of multi-stage pore graphite felt
CN121307052A